Soldier, Soldier : Diary of a Soldier - Lewis, Jonathan Guy (London Ebury, 1997)
Written by the actor who plays Sergeant McCleod, this is an insider's guide to the making of the seventh series of "Soldier, Soldier", which was partly filmed in Zimbabwe. The text contains diaries of the filming, combined with pictures and interviews with other cast members and the crew.
Include Illustrations
Keywords: Television series